2011
DOI: 10.1007/s12265-011-9304-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Gel Composed of Native Heart Matrix and Collagen Induces Cardiac Differentiation of Human Embryonic Stem Cells without Supplemental Growth Factors

Abstract: Our goal was to assess the ability of native heart extracellular matrix (ECM) to direct cardiac differentiation of human embryonic stem cells (hESCs) in vitro. In order to probe the effects of cardiac matrix on hESC differentiation, a series of hydrogels was prepared from decellularized ECM from porcine hearts by mixing ECM and collagen type I at varying ratios. Maturation of cardiac function in embryoid bodies formed from hESCs was documented in terms of spontaneous contractile behavior and the mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
139
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 42 publications
3
139
0
1
Order By: Relevance
“…18 Similarly, the ECM derived from cardiac tissue has been shown to enhance cardiomyocyte maturation of rat cardiac progenitor cells 59 and human embryonic stem cells. 60 Together with our studies, these results suggest that ColI might have a dampening effect on early differentiation of cardiomyocytes or it may impact on the growth and division of cardiomyocytes or their precursors through a mechanism we do not yet understand. The imaging techniques we describe here, because they can be performed on live cultures without manipulation required of staining protocols, could be used to better understand the relationship between ECM components and differentiation.…”
Section: Discussionsupporting
confidence: 63%
“…18 Similarly, the ECM derived from cardiac tissue has been shown to enhance cardiomyocyte maturation of rat cardiac progenitor cells 59 and human embryonic stem cells. 60 Together with our studies, these results suggest that ColI might have a dampening effect on early differentiation of cardiomyocytes or it may impact on the growth and division of cardiomyocytes or their precursors through a mechanism we do not yet understand. The imaging techniques we describe here, because they can be performed on live cultures without manipulation required of staining protocols, could be used to better understand the relationship between ECM components and differentiation.…”
Section: Discussionsupporting
confidence: 63%
“…[2][3][4][5][6] An attractive alternative is the tissue engineering approach, where three-dimensional (3D) structural control and tissue maturation before implantation are possible. 7 Many groups have had considerable success forming contractile cardiac constructs within native soft biological hydrogels, such as fibrin, 8,9 collagen, [10][11][12] and decellularized heart matrix, 13 as well as in scaffold-free conditions. 14,15 Engineering large scale cardiac tissues, however, continues to be hindered by a lack of vasculature and poor structural and functional maturation of stem cell-derived cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[79][80][81] Recently, both 2D and 3D cardiac patches were fabricated by differentiating human ESCs into cardiomyocytes in fibrin-based matrices. 79 After 2 weeks of culture, highly functionalized cardiac tissues were formed by the alignment of ESCs in microfabricated hydrogel matrices containing staggered elliptical pores (Figure 4).…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%
“…80 Human ESC-derived cardiomyocytes were encapsulated in hybrid hydrogels composed of decellularized cardiac ECM from porcine heart and collagen type I. It was found that the population of ESCs that express troponin T increased when a hydrogel with higher concentration of ECM was used.…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%
See 1 more Smart Citation